High peritoneal transport status was not associated with mortality in peritoneal dialysis patients with diabetes. - Naya Huang; Jiehui Chen; Li Fan; Qian Zhou; Qingdong Xu; Ricong Xu; Liping Xiong; Xueqing Yu; Haiping Mao (PLoS ONE, 2014)
Continuous ambulatory peritoneal dialysis (CAPD) patients with diabetes are at increased risk of mortality and high peritoneal transporters appear to contribute to poor survival. However, little is known about the combined impacts of high peritoneal transporters and diabetes on mortality.This was a prospective observational cohort study. 776 incident CAPD patients were enrolled. Unadjusted and adjusted Cox proportional regression models were used to evaluate the association and interaction of peritoneal transport and diabetic status with mortality.In the entire cohort, high peritoneal transport status was associated with an increased risk of all-cause mortality in unadjusted model [hazard ratio (HR) 2.35, 95% confidence interval (CI) 1.30 to 4.25, P = 0.01], but this association was not significant in multivariable model. There was an interaction between peritoneal membrane transport status and diabetes (P = 0.028). Subgroup analyses showed that compared to low and low average transporters, high transporters was associated with a higher risk of all-cause mortality (adjusted HR 1.78, 95% CI 1.07 to 4.70, P = 0.04) in CAPD patients without diabetes, but not in those with diabetes (adjusted HR 0.79, 95%CI 0.33 to 1.89, P = 0.59). Results were similar when transport status was assessed as a continuous variable.The association between high peritoneal transport and all-cause mortality was likely to vary with diabetes status. High peritoneal transport was associated with an elevated risk of death among CAPD patients without diabetes, but not in those with diabetes.